2018
DOI: 10.4103/ejim.ejim_24_18
|View full text |Cite
|
Sign up to set email alerts
|

Fetuin-A level in type 2 diabetic patients: relation to microvascular complications

Abstract: Background Fetuin-A is a hepatic secretory protein that binds to insulin receptors and inhibits insulin resistance (IR) kinase activity as well as IR autophosphorylation in vivo and in vitro. Aim This study aimed to investigate fetuin-A levels in patients with type 2 diabetes mellitus (T2DM) and their relation to microvascular complications. Patients and methods This descriptive study was conducted on 160 patients. Group 1 included (n=40) diabetic patients without microvascular complications, group 2 (n=40) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
3
2
0
Order By: Relevance
“…The goal of this study was to determine the Fetuin-A level as a marker that may help in the early diagnosis of DR. We observed a highly significant difference in FBG, 2HPP, and HbA1c between the studied groups (p< 0.001). This was in agreement with Al-Said et al [7], who found a significant difference in the mean levels of FBG in the diabetic without complications group versus the DR group. But in contrast to our study, Al-Said et al [7] concluded that there were no significant differences were detected in the mean levels of 2HPP between the diabetic without complications group and the DR group.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The goal of this study was to determine the Fetuin-A level as a marker that may help in the early diagnosis of DR. We observed a highly significant difference in FBG, 2HPP, and HbA1c between the studied groups (p< 0.001). This was in agreement with Al-Said et al [7], who found a significant difference in the mean levels of FBG in the diabetic without complications group versus the DR group. But in contrast to our study, Al-Said et al [7] concluded that there were no significant differences were detected in the mean levels of 2HPP between the diabetic without complications group and the DR group.…”
Section: Discussionsupporting
confidence: 93%
“…This was in agreement with Al-Said et al [7], who found a significant difference in the mean levels of FBG in the diabetic without complications group versus the DR group. But in contrast to our study, Al-Said et al [7] concluded that there were no significant differences were detected in the mean levels of 2HPP between the diabetic without complications group and the DR group. This may be attributed to the poor glycemic control and lifestyle changes of the studied patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This may project to increase 134 million by 2045. 1,2 Due to its complex pathophysiology, several biomarkers have been studied for identifying its vascular complications. However, many of these biomarkers were related to inflammation, metabolic or procoagulant.…”
Section: Introductionmentioning
confidence: 99%
“…Schmid glycoprotein) is 55-59 kDa an endogenous a 55-59 kDa phosphorylated glycoprotein which produced predominantly in the hepatocytes and secreted into serum [8], play a key role in the safety from vascular calcification by solubilizing calcium and phosphorus in serum [9], is an antiinflammatory glycoprotein declined during systemic inflammatory process that is to say it is a negative acute phase reactant. Lp(a) is a Lipoprotein that contains similar to low density lipoprotein (LDL) apolipoprotein B and in addition apolipoprotein(a) which is attached by a disulfide bridge [10].…”
Section: Fetuin-a (Human Fetuin-a or Alpha-2 Heremansmentioning
confidence: 99%